การประยุกต์ใช้ระบบการรับรองแบบมีส่วนร่วมเพื่อส่งเสริมการเกษตรอินทรีย์ภายในชุมชนเกษตรกรรายย่อย - มณีโชติ สวรรค์; อธินุวัฒน์ ดุสิต (Thai Journal of Science and Technology, 2019)
Abstract The PGS (participatory guarantee system) organic lover group was founded since 2009 with 8 small grower members within the village to produce GAP vegetables. Subsequently, the group has increased to 15 grower members and has changed the production system to be organic farming. Only one member from 15 had been gained organic standard certified by third party certification body of IFOAM and Organic Thailand since 2014. Therefore, their vegetable product was not enough to supply their entrepreneur and consumers. The 14 grower members leftover also required the organic standard certification. Even though, one of the members who has passed the organic farm certification but the certification was covered only 1 year. Besides, organic standard certification for 15 grower members causes very high certification fee each year. PGS is a tool to drive the organic certification by farmer cross checking and monitoring within the community. After 2 years, PGS was applied to the group, the members were cross checked each other farm members and followed the process. We found that 14 grower members could pass organic farm certification by PGS process, and another one would pass in next year depending on crop type and a differential of transition period. It is a result of learning process and participation of farm monitoring made clear understanding and a strict following in the organic standard. This indicated that PGS was suitable for organic farming extension within small farmer community, which carried a little various organic products and promoted a strong sustainable community. Keywords: PGS organic lover group; Chum Ta Bong; PGS; organic farming folk way; guarantee by the community